Preparation and application method of pine needle organic compost
By using modified concave and convex rods, compounded microcapsules and crosslinked network structure aerogels in organic composting technology, the problems of nutrient loss and low microbial activity are solved, and efficient soil organic matter improvement and plant growth promotion effects are achieved.
Patent Information
- Application Number
- CN202411868739.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing organic composting technology, there is a large loss of nutrients and low microbial activity, which fails to effectively improve the soil organic matter content, and microbial species are easily affected by the soil environment, resulting in inhibition of activity.
By mixing potassium sulfate, wood ash, modified concave and convex rods, borax, pine needles and rapeseed cakes for puffing treatment, combined with fermentation and drying steps, compound microcapsules are prepared, and aerogel with cross-linking network structure is used to form a cross-linking network structure to enhance the adsorption performance of fertilizers.
It improves the water retention, fertilizer retention and comprehensive utilization efficiency of fertilizers, extends the stability of soil organic matter, enhances the effect of plant growth and soil environment improvement, and avoids the loss of beneficial components.
Smart Images

Figure BDA0005195199750000192 
Figure BDA0005195199750000201
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic fertilizers, and in particular to a method for preparing and applying pine needle organic compost. Background Art
[0002] Organic composting is a process of producing organic fertilizer. It is rich in nutrients and has a long and stable fertilizer effect. It is also beneficial to promote the formation of soil solid particle structure, increase the soil's ability to retain water, heat, air and fertilizer, and mix it with chemical fertilizers to make up for the defects of chemical fertilizers containing a single nutrient, long-term single use of chemical fertilizers causing soil compaction and reduced water and fertilizer retention capabilities. Organic composting is an organic fertilizer made from various organic wastes (such as crop straw, weeds, leaves, peat, organic domestic waste, kitchen waste, sludge, human and animal feces and urine, distiller's grains, mushroom bran and other wastes) as the main raw materials, which are made through composting and decomposition.
[0003] Organic fertilizer complexes are quickly made through factory-based procedures such as crushing, high temperature, composting, and granulation. They have large nutrient loss and low fertilizer microbial activity, and fail to effectively increase the soil organic matter content, affecting the effect of organic fertilizer. Introducing microbial strains into organic fertilizers can effectively improve fertilizer utilization, promote plant growth, and improve the soil environment. However, microbial strains are easily affected by soil temperature, humidity, and pH, which inhibits the activity of the microbial strains, thereby affecting the effect of microbial organic composting. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation and application method of pine needle organic compost: attapulgite powder is thermally modified to induce tiny cracks, and the crystal water in the attapulgite is further removed to form a large number of gaps and holes, which show better adsorption performance for nutrient molecules in fermented products; nano hydroxyapatite is synthesized in the pores of the pretreated attapulgite to avoid stress on the modified attapulgite and fertilizer during dehydration, granulation and screening, resulting in collapse of the pores of the pretreated attapulgite, which affects the adsorption of nutrients; fermented products, seaweed extracts and modified cellulose are used as core materials, and lignin is used as wall materials to prepare composite microcapsules to avoid the loss of beneficial components of fermented products and organic fertilizers during dehydration, granulation, screening and packaging, and the composite microcapsules provide living space for composite bacteria in the fermented products; modified sepiolite, corn straw fiber and a cross-linking agent are mixed and reacted to form an aerogel with a cross-linked network structure, which has a porous structure and increases the adsorption of fertilizers.
[0005] The technical problem to be solved by the present invention is that the organic fertilizer complex is quickly made through factory-like procedures such as crushing, high temperature, composting, and granulation, and its nutrient loss is large and the fertilizer microbial activity is low, and it fails to effectively increase the soil organic matter content, affecting the effect of the organic fertilizer; introducing microbial strains into organic fertilizers can effectively improve the utilization rate of fertilizers, promote plant growth and improve the soil environment, but the microbial strains are easily affected by soil temperature, humidity, and pH, resulting in the inhibition of the activity of the microbial strains, thereby affecting the effect of microbial organic composting.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing pine needle organic compost comprises the following steps:
[0008] S1. Mix potassium sulfate, wood ash, modified attapulgite, borax, pine needles and rapeseed cake, stir evenly, grind, and perform puffing treatment to obtain a puffed product;
[0009] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting, and drying to obtain a fermented material;
[0010] S3, mixing the fermented product, seaweed extract, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0011] S4, mixing the compound microcapsules, the reinforcing filler and the organic fertilizer, stirring evenly to obtain a mixture, and dehydrating, granulating, screening and packaging the mixture to obtain organic compost.
[0012] Furthermore, the puffing treatment temperature is 80-100° C., the puffing treatment pressure is 1-1.5 MPa, and the puffing treatment time is 30-50 min.
[0013] Furthermore, the fermentation temperature is 28-32°C and the fermentation time is 10-12h.
[0014] Furthermore, the water content of the fermentation product is 5-10%.
[0015] Furthermore, the composite bacteria consisted of arbuscular mycorrhizal fungi and nitrogen-fixing bacteria at a rate of (1.3-1.7)×10 9 CFU:(1.5-1.7)×10 9 The CFU dosage ratio is mixed.
[0016] Furthermore, the nitrogen-fixing bacteria is selected from Bacillus subtilis or Bacillus licheniformis.
[0017] Furthermore, the mass ratio of potassium sulfate, wood ash, modified attapulgite, borax, pine needles and rapeseed cake is (20-40):(20-30):(3-8):(2-8):(5-10):(3-5).
[0018] Furthermore, the mass ratio of expanded material, potassium citrate and composite bacteria is (70-80):(20-30):(6-8).
[0019] Furthermore, the mass ratio of the compound microcapsules, the reinforcing filler and the organic fertilizer is (90-110):(5-10):(30-50).
[0020] Furthermore, the organic fertilizer is a humic acid fertilizer with a humic acid content of 30-40 g / L and a N+P2O5+K2O content of 200-220 g / L.
[0021] Furthermore, the composite microcapsules in step S3 are specifically prepared by the following steps:
[0022] A1. Wash the seaweed, dry it and crush it, add the crushed seaweed to ethanol and deionized water, extract it for 2h at 20KHz, power of 500w, temperature of 55°C, collect the filtrate by filtration, add the filtrate to a mixture of ethyl acetate and dichloromethane for extraction, evaporate the solvent from the extract to obtain a seaweed extract;
[0023] A2. Add cellulose to Tris-HCl buffer at pH 8.5, stir evenly, add dopamine, stir and react for 3.5 hours, filter, wash with deionized water three times, and dry in an oven at 70°C for 10 minutes to obtain modified cellulose;
[0024] A3. The fermented product, seaweed extract, modified cellulose and 1.5% lignin aqueous dispersion were stirred evenly, Tween80 was added, and stirring was continued to obtain an aqueous phase, epichlorohydrin and paraffin were mixed, and stirring was performed evenly to obtain an oil phase, and the aqueous phase and the oil phase were mixed, homogenized at a speed of 18000 rpm for 2.5 min, and stirred and reacted at a speed of 300 rpm for 5 h to obtain composite microcapsules.
[0025] Furthermore, during the reaction of step A2, in the Tris-HCl buffer, dopamine can self-polymerize on the cellulose surface to form polydopamine, so that the cellulose has better adhesion, and the provided catechol functional groups can be combined with the oxygen-containing functional groups in the fermentation product and the seaweed extract through chemical bonds, so that the fermentation product and the seaweed extract are evenly dispersed in the composite microcapsule system.
[0026] Furthermore, during the reaction process of step A3, the fermented product, seaweed extract and modified cellulose are used as core materials, lignin is used as wall material, and epichlorohydrin is used as a cross-linking agent to prepare microcapsules, thereby preventing the loss of beneficial components of the fermented product and organic fertilizer during the dehydration, granulation, screening and packaging processes.
[0027] Furthermore, in step A1, the ratio of the crushed seaweed, ethanol and deionized water is (4-6) g: (75-85) mL: (15-25) mL.
[0028] Furthermore, in step A2, the ratio of cellulose, Tris-HCl buffer and dopamine is (1-3) g: (45-55) mL: (0.3-0.7) g.
[0029] Furthermore, in step A3, the ratio of the fermented product, seaweed extract, modified cellulose, lignin aqueous dispersion and Tween80 is (2-3) g:(1-2) g:(1-1.4) g:(25-35) mL:(0.1-0.3) mL.
[0030] Furthermore, in step A3, the volume ratio of epichlorohydrin to paraffin is (0.2-0.4):(15-17).
[0031] Furthermore, in step A3, the volume ratio of the water phase to the oil phase is (25-35):(15-25).
[0032] Furthermore, the modified attapulgite is prepared by thermally modifying the attapulgite and then mixing it with calcium hydroxide and phosphoric acid.
[0033] Furthermore, the particle size of the attapulgite is 10-20 μm.
[0034] Furthermore, the thermal modification temperature is 280-320°C, and the thermal modification time is 2-4h.
[0035] Further, the modified attapulgite is prepared by the following steps:
[0036] B1. The attapulgite was placed on a crucible, calcined at 300 ° C for 3 h, cooled to room temperature, washed three times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain a pretreated attapulgite;
[0037] B2. Mix a 1.2 mol / L calcium hydroxide aqueous solution and a 0.6 mol / L phosphoric acid aqueous solution, stir evenly, add the pretreated attapulgite, stir at 400 rpm for 30 min, heat to 60°C, stir to react for 2 h, cool to room temperature, filter, wash 3 times with deionized water, and dry in an oven at 65°C for 10 min to obtain modified attapulgite.
[0038] Furthermore, during the reaction process of step B1, the attapulgite powder is calcined at 300° C., which causes the moisture in the attapulgite to volatilize, generates stress inside the attapulgite, and then causes tiny cracks. The crystal water in the attapulgite is further removed, forming a large number of gaps and holes, thereby obtaining a pretreated attapulgite.
[0039] Furthermore, during the reaction process of step B2, the gaps and pores of the pretreated attapulgite have excellent adsorption properties, and can adsorb calcium ions in calcium hydroxide onto the surface and pores of the heat-modified attapulgite, and the calcium ions can also combine with phosphate to form a calcium phosphate complex. After hydrothermal treatment, the calcium phosphate complex crystallizes to form nano-hydroxyapatite, thereby realizing the synthesis of nano-hydroxyapatite in the pores of the pretreated attapulgite.
[0040] Furthermore, in step B2, the ratio of calcium hydroxide aqueous solution, phosphoric acid aqueous solution, and pretreated attapulgite is (2-4) mL: (2-3) mL: (2-4) g.
[0041] Furthermore, the reinforcing filler is prepared by mixing and reacting modified sepiolite, corn straw fiber and a cross-linking agent, and then freeze-drying;
[0042] Furthermore, the modified sepiolite is prepared by mixing sepiolite with zinc acetate dihydrate after surface treatment with hydrochloric acid.
[0043] Furthermore, the particle size of the sepiolite is 0.3-1 μm, and the pore size is 20-30 nm.
[0044] Furthermore, the concentration of hydrochloric acid is 0.5-1.5 mol / L.
[0045] Furthermore, the diameter of the corn stalk fiber is 10-20 μm, the length is 1-3 mm, and the water absorption rate is 10-12%.
[0046] Furthermore, the cross-linking agent is epichlorohydrin.
[0047] Further, the reinforcing filler is specifically prepared by the following steps:
[0048] C1. The sepiolite was placed in a three-necked flask, hydrochloric acid with a concentration of 1 mol / L was added, stirred evenly, placed in a microwave oven, heated to 80°C, stirred for 2h, cooled to room temperature, washed with anhydrous ethanol 3 times, washed with deionized water until the washing liquid was neutral, placed in an oven at 60°C for 10min, and ground in a grinder to obtain pretreated sepiolite;
[0049] C2. The zinc acetate dihydrate and the pretreated sepiolite were added to deionized water, stirred evenly, sodium hydroxide was added, stirred at 300 r / min for 20 min, placed in a reactor, reacted at 120 ° C for 10 h, cooled to room temperature, the solid was removed, the solid was washed 3 times with deionized water, and dried in an oven at 80 ° C for 10 min to obtain a modified sepiolite;
[0050] C3. Add corn straw fiber to ethanol, ultrasonically treat it at 30°C for 5 minutes, add a cross-linking agent and modified sepiolite, and continue stirring to form a gel. After filtering, wash with deionized water for 3 times, and freeze-dry at -20°C for 2 hours, a composite aerogel, i.e., a reinforced filler, is obtained.
[0051] Furthermore, during the reaction process of step C1, the sepiolite is surface treated with hydrochloric acid, so that the free metal ions and magnesium ions in the sepiolite are replaced and precipitated, the surface impurities are removed, and the internal pores of the sepiolite are opened. The porous structure can adsorb organic fertilizers, thereby improving the water retention, fertilizer retention and comprehensive utilization efficiency of the organic fertilizers.
[0052] Furthermore, during the reaction process of step C2, zinc ions in zinc acetate dihydrate can be adsorbed onto the surface of the pretreated sepiolite, and hydroxide ions provided by sodium hydroxide can combine with zinc ions to form a zinc hydroxide complex. Under a hydrothermal reaction at 130° C., the zinc hydroxide complex is thermally decomposed to form zinc oxide crystals, which grow in crystallization to form nano zinc oxide in the pretreated sepiolite, thereby obtaining modified sepiolite.
[0053] Furthermore, during the reaction of step C3, the corn stalk fiber can be combined with the cross-linking agent epichlorohydrin through chemical bonds to form an aerogel with a cross-linked network structure, and the modified sepiolite is embedded in the aerogel. The formed aerogel has a porous structure, which increases the adsorption of fertilizers.
[0054] Furthermore, in step C1, the ratio of sepiolite to hydrochloric acid is (4-6) g:(35-45) mL.
[0055] Furthermore, in step C2, the ratio of zinc acetate dihydrate, pretreated sepiolite, deionized water and sodium hydroxide is (2-3) g: (3-4) g: (50-70) mL: (1-2) g.
[0056] Furthermore, in step C3, the ratio of corn straw fiber, ethanol, crosslinking agent and modified sepiolite is (2-3) g: (70-90) mL: (0.4-0.6) mL: (1-2) g.
[0057] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0058] (1) In the technical scheme of the present invention, the attapulgite powder is thermally modified to induce tiny cracks, and the crystal water in the attapulgite is further removed to form a large number of gaps and holes, which show better adsorption performance for nutrient molecules in the fermentation product; nano-hydroxyapatite is synthesized in the pores of the pretreated attapulgite. On the one hand, the synthesized nano-hydroxyapatite serves as the skeleton structure of the thermally modified attapulgite, improves the compressive strength of the thermally modified attapulgite, and avoids the modified attapulgite and fertilizer from being subjected to stress during the dehydration, granulation, and screening processes, which causes the collapse of the pores of the pretreated attapulgite, affects the adsorption of nutrients, and then causes the loss of nutrients, affecting the fertility of the compost; on the other hand, the synthesized nano-hydroxyapatite refines the pores of the pretreated attapulgite, improves the porosity, and increases the adsorption of nutrients. Hydroxyapatite is rich in phosphorus, which can improve the fertility of the soil, promote plant growth, and improve the disease resistance of plants.
[0059] (2) In the technical solution of the present invention, the seaweed extract is rich in a large number of beneficial ingredients such as polysaccharides, amino acids, proteins, vitamins, etc., which promote the growth and development of plants. The seaweed extract can neutralize the pH of the soil, optimize the soil environment, and provide a comfortable living environment for the survival of the composite bacteria. In addition, it has a good effect on the plant's resistance to cold, high temperature, drought and flood, salt and alkali, fertilizer damage, air damage, and nutritional imbalance.
[0060] (3) In the technical scheme of the present invention, polydopamine-modified cellulose has good adhesion, and the catechol functional groups provided can be combined with the oxygen-containing functional groups in the fermentation product and seaweed extract through chemical bonds, so that the fermentation product and seaweed extract are uniformly dispersed in the composite microcapsule system; the fermentation product, seaweed extract and modified cellulose are used as core materials, lignin is used as wall material, and epichlorohydrin is used as a cross-linking agent to prepare composite microcapsules, thereby avoiding the loss of beneficial components of the fermentation product and organic fertilizer during dehydration, granulation, screening and packaging, and the composite microcapsules provide a living space for the composite bacteria in the fermentation product to avoid the inactivation of the composite bacteria due to the influence of the soil environment; in addition, the modified cellulose can be interspersed between the fermentation product and the seaweed extract to form a cross-linked network structure, further enhancing the effect on the fermentation product and the seaweed extract and reducing the loss, and the organic components of the seaweed extract and the modified cellulose provide a carbon source for the composite bacteria, thereby promoting the growth and reproduction of the composite bacteria and improving soil fertility.
[0061] (4) In the technical scheme of the present invention, the porous structure of the pretreated sepiolite can adsorb organic fertilizers, thereby improving the water retention, fertilizer retention and comprehensive utilization efficiency of organic fertilizers; nano zinc oxide is formed in the pretreated sepiolite to improve the porosity of the pretreated sepiolite, which is beneficial to the adsorption of organic fertilizers; and the modified sepiolite as a fertilizer carrier has low shrinkage, good plasticity, high surface tension and strong adsorption, thereby improving the water retention, fertilizer retention and utilization efficiency of fertilizers; in addition, sepiolite and nano zinc oxide can improve soil structure, and nano zinc oxide provides plants with sufficient zinc elements to promote plant growth and development.
[0062] (5) In the technical solution of the present invention, modified sepiolite, corn straw fiber and a cross-linking agent are mixed and reacted to form an aerogel with a cross-linked network structure, which has a porous structure and increases the adsorption of fertilizers. The formed aerogel can be evenly dispersed in organic fertilizers to avoid agglomeration of modified sepiolite. In addition, the corn straw fiber in the aerogel can interact with the lignin in the compound microcapsule through chemical bonds, which is beneficial to enhance the dispersion of fillers and compound microcapsules in beneficial fertilizers and improve the fertility of organic fertilizers.
[0063] (6) In the technical solution of the present invention, plant ash, borax, pine needles and rapeseed cake are used as the basic components of pine needle organic compost. Plant ash is a loose product containing a large amount of mineral elements such as potassium, calcium, and magnesium produced after the combustion of biomass. It provides the necessary nutrients for plant growth and enhances the fertility of compost. Plant ash can also increase the air permeability and water retention of the soil, making the soil more loose and fertile, which is conducive to the growth and development of plant roots. In addition, plant ash is compounded with organic pine needles and rapeseed cake to avoid the increase of soil alkalinity caused by the use of plant ash alone, while increasing soil fertility. The boron element in borax can improve the drought resistance, cold resistance, and disease resistance of plants, enhance the adaptability of crops, and reduce the decline in plant yield due to environmental stress.
[0064] (7) In the technical scheme of the present invention, rapeseed cake is a fast-acting, comprehensive organic fertilizer, rich in nitrogen and phosphorus nutrients, providing nutrients for plant growth and promoting plant growth; pine needles can meet the nutrient needs of plants during the growth period, effectively improve the absorption of nitrogen and phosphorus elements, and promote plant growth; wood ash, pine needles and rapeseed cake organic matter are fermented with composite bacteria to form a fermentation product that is easily absorbed by plants, thereby improving the utilization rate of pine needles and rapeseed cake and promoting plant growth. The fermentation product formed can improve soil structure, improve soil water and fertilizer retention capacity, and promote the reproduction of soil microorganisms. At the same time, pine needles and rapeseed cake produce beneficial microbial flora, which helps to improve the soil environment and promote the healthy growth of plants. DETAILED DESCRIPTION
[0065] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0067] Plant ash, Guangxi Zhuangfang Liyuan Biotechnology Co., Ltd.
[0068] Pine needles, Huamao (Shandong) Biotechnology Co., Ltd.
[0069] Rapeseed cake, Hebei Mowei Mineral Products Trading Co., Ltd.
[0070] The particle size of attapulgite is 15 μm, Mingguang Zhongtian Industry and Trade Co., Ltd.
[0071] The particle size of sepiolite is 0.5μm and the pore size is 25nm, Hebei Mingzhe Mineral Products Co., Ltd.
[0072] The diameter of corn straw fiber is 15μm, the length is 2mm, and the water absorption rate is 11%.
[0073] The organic fertilizer is humic acid fertilizer with a humic acid content of 35g / L and a N+P2O5+K2O content of 210g / L, from Qingdao Leiwo Biotechnology Co., Ltd.
[0074] The nitrogen-fixing bacteria were selected from Bacillus subtilis, Jinan Qinghai Chemical Co., Ltd.
[0075] The arbuscular mycorrhizal fungi were selected from Phyllostomium mosseae, Institute of Plant Nutrition and Resources, Beijing Academy of Agricultural and Forestry Sciences.
[0076] The seaweed extract is specifically prepared by the following steps:
[0077] The seaweed was washed, dried and crushed, 5 g of the crushed seaweed was added to 80 mL of ethanol and 20 mL of deionized water, and extracted for 2 h at 20 KHz, a power of 500 W and a temperature of 55 ° C. The filtrate was collected by filtration, 3.5 mL of the filtrate was added to a mixture of 10 mL of ethyl acetate and 1.2 mL of dichloromethane for extraction, and the solvent was evaporated from the extract to obtain a seaweed extract.
[0078] The modified attapulgite of embodiment 1 is prepared by the following steps:
[0079] B1. The attapulgite was placed on a crucible, calcined at 300 ° C for 3 h, cooled to room temperature, washed three times with deionized water, and dried in an oven at 70 ° C for 10 min to obtain a pretreated attapulgite;
[0080] B2. Mix 3 mL of 1.2 mol / L calcium hydroxide aqueous solution and 2.5 mL of 0.6 mol / L phosphoric acid aqueous solution, stir evenly, add 3 g of pretreated attapulgite, stir at 400 rpm for 30 min, heat to 60 ° C, stir to react for 2 h, cool to room temperature, filter, wash 3 times with deionized water, and dry in an oven at 65 ° C for 10 min to obtain modified attapulgite.
[0081] Comparative Example 1 The difference between this comparative example and Example 1 is that the pretreated attapulgite is replaced by attapulgite, and the remaining steps and raw materials are synchronized with Example 1.
[0082] Mix 3 mL of 1.2 mol / L calcium hydroxide aqueous solution and 2.5 mL of 0.6 mol / L phosphoric acid aqueous solution, stir evenly, add 3 g of attapulgite, stir at 400 rpm for 30 min, heat to 60 ° C, stir to react for 2 h, cool to room temperature, filter, wash 3 times with deionized water, and dry in an oven at 65 ° C for 10 min to obtain modified attapulgite.
[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that nano-hydroxyapatite is not synthesized on the surface of the pretreated attapulgite, and the remaining steps and raw materials are synchronized with Example 1.
[0084] The attapulgite was placed on a crucible, calcined at 300° C. for 3 h, cooled to room temperature, washed with deionized water for 3 times, and dried in an oven at 70° C. for 10 min to obtain a modified attapulgite.
[0085] Embodiment 2 The reinforcing filler is specifically prepared by the following steps:
[0086] C1. 5 g of sepiolite was placed in a 250 mL three-necked flask, 40 mL of 1 mol / L hydrochloric acid was added, stirred evenly, placed in a microwave oven, heated to 80 ° C, stirred for 2 h, cooled to room temperature, washed with anhydrous ethanol 3 times, washed with deionized water until the washing liquid was neutral, placed in a 60 ° C oven to dry for 10 min, placed in a grinder to grind, to obtain pretreated sepiolite;
[0087] C2. 2.5 g of zinc acetate dihydrate and 3.5 g of pretreated sepiolite were added to 60 mL of deionized water, stirred evenly, 1.6 g of sodium hydroxide was added, stirred at 300 r / min for 20 min, placed in a reactor, reacted at 120 ° C for 10 h, cooled to room temperature, the solid was taken out, the solid was washed 3 times with deionized water, and dried in an oven at 80 ° C for 10 min to obtain a modified sepiolite;
[0088] C3. Add 2.5 g corn straw fiber to 80 mL ethanol, ultrasonically treat at 30 ° C for 5 min, add 0.5 mL epichlorohydrin and 1.5 g modified sepiolite, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20 ° C for 2 h to obtain a composite aerogel, i.e., a reinforced filler.
[0089] Comparative Example 3 The difference between this comparative example and Example 2 is that the modified sepiolite is replaced by pretreated sepiolite, and the remaining steps and raw materials are the same as Example 2.
[0090] C1. 5 g of sepiolite was placed in a 250 mL three-necked flask, 40 mL of 1 mol / L hydrochloric acid was added, stirred evenly, placed in a microwave oven, heated to 80 ° C, stirred for 2 h, cooled to room temperature, washed with anhydrous ethanol 3 times, washed with deionized water until the washing liquid was neutral, placed in a 60 ° C oven to dry for 10 min, placed in a grinder to grind, to obtain pretreated sepiolite;
[0091] C2. Add 2.5 g corn straw fiber to 80 mL ethanol, ultrasonically treat at 30 ° C for 5 min, add 0.5 mL epichlorohydrin and 1.5 g pretreated sepiolite, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20 ° C for 2 h to obtain a composite aerogel, i.e., a reinforced filler.
[0092] Comparative Example 4 The difference between this comparative example and Example 2 is that corn straw fiber and epichlorohydrin are not added, and the remaining steps and raw materials are synchronized with Example 2.
[0093] C1. 5 g of sepiolite was placed in a 250 mL three-necked flask, 40 mL of 1 mol / L hydrochloric acid was added, stirred evenly, placed in a microwave oven, heated to 80 ° C, stirred for 2 h, cooled to room temperature, washed with anhydrous ethanol 3 times, washed with deionized water until the washing liquid was neutral, placed in a 60 ° C oven to dry for 10 min, placed in a grinder to grind, to obtain pretreated sepiolite;
[0094] C2. Add 2.5 g of zinc acetate dihydrate and 3.5 g of pretreated sepiolite to 60 mL of deionized water, stir evenly, add 1.6 g of sodium hydroxide, stir at 300 r / min for 20 min, place in a reactor, react at 120°C for 10 h, cool to room temperature, take out the solid, wash the solid with deionized water 3 times, and dry in an oven at 80°C for 10 min to obtain a reinforced filler.
[0095] Embodiment 3 A method for preparing pine needle organic compost comprises the following steps:
[0096] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0097] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 20:20:3:2:5:3;
[0098] The puffing temperature is 80°C, the puffing pressure is 1MPa, and the puffing time is 40min;
[0099] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 5%;
[0100] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 70:20:6;
[0101] The fermentation temperature is 28°C and the fermentation time is 10h;
[0102] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.3×10 9 CFU:1.5×10 9 CFU;
[0103] S3, mixing the fermented product, seaweed extract, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0104] S4, mixing the composite microcapsules, the reinforcing filler obtained in Example 2 and the humic acid fertilizer, stirring evenly to obtain a mixture, dehydrating, granulating, screening and packaging the mixture to obtain organic compost;
[0105] Among them, the mass ratio of the compound microcapsules, the reinforced fillers and the humic acid fertilizer is 90:5:30.
[0106] The composite microcapsules are specifically prepared by the following steps:
[0107] A1. Add 1 g of cellulose to 45 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.3 g of dopamine, stir and react for 3.5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain modified cellulose;
[0108] A2. 2 g of fermentation product, 1 g of seaweed extract, 25 mL of 1 g of modified cellulose and 1.5% lignin aqueous dispersion were stirred evenly, 0.1 mL of Tween80 was added and stirred evenly to obtain an aqueous phase, 0.2 mL of epichlorohydrin and 15 mL of paraffin were mixed and stirred evenly to obtain an oil phase, 25 mL of the aqueous phase and 15 mL of the oil phase were mixed, homogenized at a speed of 18000 rpm for 2.5 min, and stirred at a speed of 300 rpm for 5 h to obtain composite microcapsules.
[0109] Embodiment 4 A method for preparing pine needle organic compost comprises the following steps:
[0110] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0111] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 30:25:6:6:8:4;
[0112] The puffing temperature is 90°C, the puffing pressure is 1.3MPa, and the puffing time is 40min.
[0113] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 8%;
[0114] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 75:25:7;
[0115] The fermentation temperature is 30°C and the fermentation time is 11h;
[0116] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.4×10 9 CFU:1.6×10 9 CFU;
[0117] S3, mixing the fermented product, seaweed extract, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0118] S4, mixing the composite microcapsules, the reinforcing filler obtained in Example 2 and the humic acid fertilizer, stirring evenly to obtain a mixture, dehydrating, granulating, screening and packaging the mixture to obtain organic compost;
[0119] Among them, the mass ratio of the composite microcapsules, the reinforced filler prepared in Example 2 and the humic acid fertilizer is 100:8:40.
[0120] The composite microcapsules are specifically prepared by the following steps:
[0121] A1. Add 2 g of cellulose to 50 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.5 g of dopamine, stir and react for 3.5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain modified cellulose;
[0122] A2. 2.5 g of fermentation product, 1.5 g of seaweed extract, 30 mL of 1.2 g of modified cellulose and 1.5% lignin aqueous dispersion were stirred evenly, 0.2 mL of Tween80 was added and stirred evenly to obtain an aqueous phase, 0.3 mL of epichlorohydrin and 16 mL of paraffin were mixed and stirred evenly to obtain an oil phase, 30 mL of the aqueous phase and 20 mL of the oil phase were mixed, homogenized at a speed of 18000 rpm for 2.5 min, and stirred at a speed of 300 rpm for 5 h to obtain composite microcapsules.
[0123] Embodiment 5 A method for preparing pine needle organic compost comprises the following steps:
[0124] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0125] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 40:30:8:8:10:5;
[0126] The puffing temperature is 100°C, the puffing pressure is 1.5MPa, and the puffing time is 50min;
[0127] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 10%;
[0128] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 80:30:8;
[0129] The fermentation temperature is 32°C and the fermentation time is 12h;
[0130] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.5×10 9 CFU:1.7×10 9 CFU;
[0131] S3, mixing the fermented product, seaweed extract, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0132] S4, mixing the composite microcapsules, the reinforcing filler obtained in Example 2 and the humic acid fertilizer, stirring them evenly to obtain a mixture, and dehydrating, granulating, screening and packaging the mixture to obtain organic compost.
[0133] The mass ratio of the composite microcapsules, the reinforced filler prepared in Example 2 and the humic acid fertilizer is 110:10:50.
[0134] The composite microcapsules are specifically prepared by the following steps:
[0135] A1. Add 3 g of cellulose to 55 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.7 g of dopamine, stir and react for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain modified cellulose;
[0136] A2. Stir 3 g of fermentation product, 2 g of seaweed extract, 35 mL of 1.4 g of modified cellulose and 1.5% lignin aqueous dispersion with a mass fraction, add 0.3 mL of Tween80, stir evenly to obtain an aqueous phase, mix 0.4 mL of epichlorohydrin and 17 mL of paraffin, stir evenly to obtain an oil phase, mix 35 mL of the aqueous phase and 25 mL of the oil phase, homogenize at a speed of 18000 rpm for 2.5 min, stir and react at a speed of 300 rpm for 5 h, and obtain composite microcapsules.
[0137] Comparative Example 5 The difference between this comparative example and Example 4 is that the modified attapulgite prepared in Example 1 is replaced by the material prepared in Comparative Example 1, and the remaining steps are synchronized with Example 4.
[0138] Comparative Example 6 The difference between this comparative example and Example 4 is that the modified attapulgite prepared in Example 1 is replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 4.
[0139] Comparative Example 7 The difference between this comparative example and Example 4 is that the reinforcing filler prepared in Example 2 is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 4.
[0140] Comparative Example 8 The difference between this comparative example and Example 4 is that the reinforcing filler prepared in Example 2 is replaced by the material prepared in Comparative Example 4, and the remaining steps are synchronized with Example 4.
[0141] Comparative Example 9 The difference between this comparative example and Example 4 is that cellulose is not added in step S3, and the remaining steps are synchronized with Example 4.
[0142] A method for preparing pine needle organic compost comprises the following steps:
[0143] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0144] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 30:25:6:6:8:4;
[0145] The puffing temperature is 90°C, the puffing pressure is 1.3MPa, and the puffing time is 40min.
[0146] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 8%;
[0147] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 75:25:7;
[0148] The fermentation temperature is 30°C and the fermentation time is 11h;
[0149] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.4×10 9 CFU:1.6×10 9 CFU;
[0150] S3, mixing the fermented product, seaweed extract, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0151] S4, mixing the composite microcapsules, the reinforcing filler obtained in Example 2 and the humic acid fertilizer, stirring evenly to obtain a mixture, dehydrating, granulating, screening and packaging the mixture to obtain organic compost;
[0152] Among them, the mass ratio of the composite microcapsules, the reinforced filler prepared in Example 2 and the humic acid fertilizer is 100:8:40.
[0153] The composite microcapsules are specifically prepared by the following steps:
[0154] 2.5 g of fermentation product, 1.5 g of seaweed extract and 30 mL of 1.5% mass% lignin aqueous dispersion were stirred evenly, 0.2 mL of Tween80 was added and stirred evenly to obtain an aqueous phase, 0.3 mL of epichlorohydrin and 16 mL of paraffin were mixed and stirred evenly to obtain an oil phase, 30 mL of the aqueous phase and 20 mL of the oil phase were mixed, homogenized at a speed of 18000 rpm for 2.5 min, and stirred and reacted at a speed of 300 rpm for 5 h to obtain composite microcapsules.
[0155] Comparative Example 10 The difference between this comparative example and Example 4 is that no seaweed extract is added in step S3, and the remaining steps are synchronized with Example 4.
[0156] A method for preparing pine needle organic compost comprises the following steps:
[0157] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0158] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 30:25:6:6:8:4;
[0159] The puffing temperature is 90°C, the puffing pressure is 1.3MPa, and the puffing time is 40min.
[0160] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 8%;
[0161] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 75:25:7;
[0162] The fermentation temperature is 30°C and the fermentation time is 11h;
[0163] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.4×10 9 CFU:1.6×10 9 CFU;
[0164] S3, mixing the fermented product, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules;
[0165] S4, mixing the composite microcapsules, the reinforcing filler obtained in Example 2 and the humic acid fertilizer, stirring evenly to obtain a mixture, dehydrating, granulating, screening and packaging the mixture to obtain organic compost;
[0166] Among them, the mass ratio of the composite microcapsules, the reinforced filler prepared in Example 2 and the humic acid fertilizer is 100:8:40.
[0167] The composite microcapsules are specifically prepared by the following steps:
[0168] A1. Add 2 g of cellulose to 50 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.5 g of dopamine, stir and react for 3.5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain modified cellulose;
[0169] A2. 2.5 g of fermentation product, 1.2 g of modified cellulose and 30 mL of 1.5% lignin aqueous dispersion were stirred evenly, 0.2 mL of Tween80 was added and stirred evenly to obtain an aqueous phase, 0.3 mL of epichlorohydrin and 16 mL of paraffin were mixed and stirred evenly to obtain an oil phase, 30 mL of the aqueous phase and 20 mL of the oil phase were mixed, homogenized at 18000 rpm for 2.5 min, and stirred at 300 rpm for 5 h to obtain composite microcapsules.
[0170] Comparative Example 11 The difference between this comparative example and Example 4 is that step S3 does not perform microcapsule coating, and the remaining steps are synchronized with Example 4.
[0171] A method for preparing pine needle organic compost comprises the following steps:
[0172] S1, mixing potassium sulfate, wood ash, the modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake, stirring evenly, grinding, and then puffing to obtain a puffed product;
[0173] Among them, the mass ratio of potassium sulfate, wood ash, modified attapulgite prepared in Example 1, borax, pine needles and rapeseed cake is 30:25:6:6:8:4;
[0174] The puffing temperature is 90°C, the puffing pressure is 1.3MPa, and the puffing time is 40min.
[0175] S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting and drying to obtain a fermented product, wherein the water content of the fermented product is 8%;
[0176] Among them, the mass ratio of expanded material, potassium citrate and composite bacteria is 75:25:7;
[0177] The fermentation temperature is 30°C and the fermentation time is 11h;
[0178] The composite bacteria consisted of arbuscular mycorrhizal fungi and Bacillus subtilis in a ratio of 1.4×10 9 CFU:1.6×10 9 CFU;
[0179] S3, mixing the fermented product, the seaweed extract and the modified cellulose to obtain a compound;
[0180] S4, mixing the composite material, the reinforcing filler prepared in Example 2 and the humic acid fertilizer, stirring evenly to obtain a mixture, and dehydrating, granulating, screening and packaging the mixture to obtain organic compost;
[0181] Among them, the mass ratio of the compound, the reinforcing filler prepared in Example 2 and the humic acid fertilizer is 100:8:40.
[0182] The modified cellulose is specifically prepared by the following steps:
[0183] 2 g of cellulose was added to 50 mL of Tris-HCl buffer at pH 8.5, stirred evenly, 0.5 g of dopamine was added, stirred and reacted for 3.5 h, filtered, washed with deionized water 3 times, and dried in an oven at 70° C. for 10 min to obtain modified cellulose.
[0184] The performance of the organic composts prepared in Examples 3-5 and Comparative Examples 5-11 was tested.
[0185] The organic matter and nutrient content of the organic compost prepared above were tested according to "NY525-2012 Organic Fertilizer", wherein the organic matter was determined by potassium dichromate volumetric method, the total nitrogen was determined by Kjeldahl nitrogen analyzer, the phosphorus content was determined by spectrophotometry, and the potassium content was determined by flame photometry. Commercially available organic compost was used as a control group. The measurement data are shown in Table 1 below:
[0186] Table 1
[0187]
[0188]
[0189] The organic compost prepared in Examples 3-5 and Comparative Examples 5-11 is now applied, specifically:
[0190] The prepared organic compost is spread on the soil and then tilled into the soil. Corn and wheat are planted in the soil spread with the prepared organic compost respectively. The crops are harvested after 120 days and the yields are calculated to determine the yield-increasing effect of the fertilizer.
[0191] The test results are shown in Table 2 below:
[0192] Table 2
[0193] project Corn yield (kg / mu) Wheat yield (kg / mu) Example 3 625 725 Example 4 630 730 Example 5 623 721 Comparative Example 5 432 475 Comparative Example 6 411 456 Comparative Example 7 465 496 Comparative Example 8 445 483 Comparative Example 9 403 462 Comparative Example 10 417 471 Comparative Example 11 403 441
[0194] It can be seen from the data in Table 1 and Table 2 that when the modified attapulgite prepared by replacing the pretreated attapulgite in Comparative Example 5 with attapulgite was added to the organic compost, the nutrient content of the fertilizer decreased and the crop yield decreased. This may be because the attapulgite powder was thermally modified, which caused tiny cracks, and the further removal of the crystalline water in the attapulgite formed a large number of gaps and holes, which showed better adsorption performance for the nutrient molecules in the fermentation product.
[0195] In Comparative Example 6, the modified attapulgite prepared without synthesizing nano-hydroxyapatite on the surface of the pretreated attapulgite was added to the organic compost. The nutrient content of the fertilizer decreased and the crop yield decreased. This may be because the nano-hydroxyapatite was synthesized in the pores of the pretreated attapulgite, which prevented the modified attapulgite from collapsing, affecting the adsorption of nutrients, thereby causing the loss of nutrients and affecting the fertility of the compost.
[0196] In Comparative Example 7, the modified sepiolite is replaced with a reinforcing filler prepared from pretreated sepiolite and added to the organic compost. The nutrient content of the fertilizer decreases and the crop yield decreases. This may be because the porous structure of the pretreated sepiolite can absorb organic fertilizers, thereby improving the water retention, fertilizer retention and comprehensive utilization efficiency of organic fertilizers.
[0197] In Comparative Example 8, the reinforcing filler prepared without adding corn straw fiber and epichlorohydrin was added to the organic compost, and the nutrient content of the fertilizer decreased, and the crop yield decreased. This may be because the corn straw fiber and the cross-linking agent were mixed and reacted to form an aerogel with a cross-linked network structure, which has a porous structure and increases the adsorption of fertilizer. The formed aerogel can be evenly dispersed in the organic fertilizer, avoiding the agglomeration of the modified sepiolite; it is beneficial to disperse the reinforcing filler and the compound microcapsule in the favorable fertilizer, thereby improving the fertility of the organic fertilizer.
[0198] In Comparative Example 9, when the composite microcapsules prepared without adding cellulose were added to organic compost, the nutrient content of the fertilizer decreased and the crop yield decreased. This may be because cellulose was interspersed between the fermentation product and the seaweed extract to form a cross-linked network structure, which further enhanced the effect on the fermentation product and the seaweed extract and reduced loss. In addition, the organic components of the modified cellulose provided a carbon source for the composite bacteria, promoted the growth and reproduction of the composite bacteria, and improved soil fertility.
[0199] In Comparative Example 10, the reinforcing filler prepared without adding seaweed extract was added to the organic compost, and the nutrient content of the fertilizer decreased, and the crop yield decreased. This may be because the seaweed extract is rich in a large number of beneficial ingredients such as polysaccharides, amino acids, proteins, vitamins, etc., which promote the growth and development of plants. The organic components of the seaweed extract provide a carbon source for the composite bacteria, promote the growth and reproduction of the composite bacteria, and improve soil fertility.
[0200] In comparative example 11, the compound without microcapsule preparation in step S3 was added to the organic compost, and the nutrient content of the fertilizer decreased, and the crop yield decreased. This may be because the compound microcapsules prevented the loss of beneficial components of the fermentation product and the organic fertilizer during the dehydration, granulation, screening and packaging processes, and the compound microcapsules provided a living space for the composite strains in the fermentation product, preventing the composite strains from being inactivated by the soil environment.
[0201] The data in Table 1 and Table 2 show that the organic composts prepared in Examples 3-5 meet the test performance requirements, while the organic composts prepared in Comparative Examples 5-11 do not meet the performance requirements, indicating that the organic composts prepared in the present invention can promote plant growth.
[0202] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0203] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing pine needle organic compost, characterized in that: The following steps are involved: S1. Mix potassium sulfate, wood ash, modified attapulgite, borax, pine needles and rapeseed cake, stir evenly, grind, and perform puffing treatment to obtain a puffed product; S2, mixing the expanded material, potassium citrate and the composite bacteria evenly, fermenting, and drying to obtain a fermented material; S3, mixing the fermented product, seaweed extract, modified cellulose, Tween80 and lignin aqueous dispersion as the aqueous phase, and mixing epichlorohydrin and paraffin as the oil phase to prepare composite microcapsules; S4, mixing the composite microcapsules, the reinforcing filler and the organic fertilizer, stirring evenly to obtain a mixture, and dehydrating, granulating, screening and packaging the mixture to obtain organic compost; The modified attapulgite is prepared by thermally modifying the attapulgite and then mixing it with calcium hydroxide and phosphoric acid for reaction; The reinforcing filler is prepared by mixing modified sepiolite, corn stalk fiber and a cross-linking agent, followed by freeze drying; The modified sepiolite is prepared by mixing sepiolite with zinc acetate dihydrate after the surface of the sepiolite is treated with hydrochloric acid.
2. The method for preparing pine needle organic compost according to claim 1, characterized in that: The attapulgite particle size is 10-20 μm; the thermal modification temperature is 280-320° C., and the thermal modification time is 2-4 hours.
3. The method for preparing pine needle organic compost according to claim 1, characterized in that: The particle size of the sepiolite is 0.3-1 μm, and the pore size is 20-30 nm; the concentration of the hydrochloric acid is 0.5-1.5 mol / L.
4. The method for preparing pine needle organic compost according to claim 1, characterized in that: The corn stalk fiber has a diameter of 10-20 μm, a length of 1-3 mm, and a water absorption rate of 10-12%.
5. The method for preparing pine needle organic compost according to claim 1, characterized in that: In step S1, the puffing treatment temperature is 80-100°C, the puffing treatment pressure is 1-1.5MPa, and the puffing treatment time is 30-50min.
6. The method for preparing pine needle organic compost according to claim 1, characterized in that: In step S2, the fermentation temperature is 28-32°C, the fermentation time is 10-12 hours, and the water content of the fermented product is 5-10%.
7. The method for preparing pine needle organic compost according to claim 1, characterized in that: In step S3, the modified cellulose is specifically prepared by the following steps: adding cellulose to Tris-HCl buffer, stirring evenly, adding dopamine, stirring for reaction, filtering, washing, and drying for 10 minutes to obtain modified cellulose.
8. The method for preparing pine needle organic compost according to claim 1, characterized in that: In step S4, the organic fertilizer is humic acid fertilizer, with a humic acid content of 30-40 g / L and a N+P2O5+K2O content of 200-220 g / L.
9. The method for preparing pine needle organic compost according to claim 1, characterized in that: The composite bacteria species are composed of arbuscular mycorrhizal fungi and nitrogen-fixing bacteria according to (1.3-1.7)×10 9 CFU:(1.5-1.7)×10 9 The nitrogen-fixing bacteria are selected from Bacillus subtilis or Bacillus licheniformis.
10. A method for applying the organic compost prepared according to any one of claims 1 to 9, characterized in that: The specific application method is: spreading the organic compost on the soil and then tilling it into the soil.
Citation Information
Patent Citations
Sepiolite supported nano zinc oxide photocatalysis material and preparation method thereof
CN101352677A
Method for producing filter material for removing fluorine from drinking water
CN101913584A
Production method of attapulgite loaded hydroxyapatite composite defluorination filter bulb
CN102502907A
Fertilizer specially used for cucumber planting, and preparation method of fertilizer
CN108314545A
Soil remediation agent based on microelement coal gangue and preparation method of soil remediation agent
CN117903809A
Cited By
Bio-fertilizer for promoting high yield of safflower and fertilizing method thereof
CN120463563A